2016
DOI: 10.1186/s13256-016-1037-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic hepatic portal venous gas with gastric emphysema as a chronic complication of gastrostomy tube placement: a case report

Abstract: BackgroundPercutaneous endoscopic gastrostomy feeding is widely used as a route for enteral feeding for patients with impaired swallowing ability, particularly in older patients. Hepatic portal venous gas is a condition that may arise from several causes. Hepatic portal venous gas that develops after an endoscopic procedure is generally reported to be nonfatal, yet there is little information available concerning the characteristics of hepatic portal venous gas as a chronic complication of percutaneous endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In cases where clinical presentation and radiological findings remain inconclusive, it is better to perform urgent endoscopy or diagnostic laparoscopy 12. Follow-up CT scan usually shows resolution of air in 3–4 days suggesting a favourable prognosis of gastric emphysema even with the presence of hepatic portal venous gas in uncomplicated individuals 13. In this review, initial conservative treatment was employed in most of the cases.…”
Section: Discussionmentioning
confidence: 92%
“…In cases where clinical presentation and radiological findings remain inconclusive, it is better to perform urgent endoscopy or diagnostic laparoscopy 12. Follow-up CT scan usually shows resolution of air in 3–4 days suggesting a favourable prognosis of gastric emphysema even with the presence of hepatic portal venous gas in uncomplicated individuals 13. In this review, initial conservative treatment was employed in most of the cases.…”
Section: Discussionmentioning
confidence: 92%
“…Kim et al (2020) reported that there was additional leukocytosis and an increase in C-reactive protein level at the time of patient admission. Sawano et al (2016) reported hepatic portal venous gas, leukocytosis, and elevation of C-reactive protein in addition to GE. They discontinued enteral nutrition by starting antibiotic therapy and parenteral nutrition at the time of diagnosis and reported that GE regressed without the need to remove the PEG tube.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HPVG with pneumatosis intestinalis (PI) indicates a high probability of bowel gangrene [7] and high mortality; 49% mortality with PI and 29% without PI [8]. Although mechanism is not well understood, it is associated with bowel distension, elevation of digestive tract pressure, endoscopic procedures, mucosal damage, sepsis, and gas embolization among others [4,9,10].…”
Section: Discussionmentioning
confidence: 99%